Thickness and marking quality of different occlusal contact registration strips - Maria Fernanda de Souza Mauá Serapião TOLEDO; Renata Pilli JÓIAS; Yves Santini MARQUES-IASI; Ana Christina Claro NEVES; Sigmar de Mello RODE (University of São Paulo, 2014)
Objectives Evaluate the thickness and the marking quality of different occlusal contact registration strips (OCRS) and a possible correlation between them. Material and Methods The following OCRS were selected: Accufilm II, BK20, BK21, BK22, BK23, BK28, and BK31. The thickness was measured in three points of the OCRS with an electronic measuring device (TESA), and the mean was calculated. To produce the marks on the strips, composite resin specimens were adapted to a universal testing machine (Versat 2000) with 40 kgf load cell at a speed of 1.0 mm/min. The mark images were photographed with a stereoscopic microscope (Stemi SV11) and processed and analyzed by the 550-Leica Qwin® analyzer. Results Values (μm) found in the 1st and 2nd thickness measurements were: Accufilm II - 16.4 and 14.2; BK20 - 10.0 and 8.1; BK21 - 9.5 and 8.0; BK22 - 9.7 and 8.7; BK23 - 9.8 and 7.9; BK28 - 12.8 and 10.0; and BK31 - 8.4 and 8.0, respectively. The mean (mm2) values found in the mark areas were: Accufilm II - 0.078; BK20 - 0.035; BK21 - 0.045; BK22 - 0.012; BK23 - 0.022; BK28 - 0.024; and BK31 - 0.024. The results were submitted to the Kruskal-Wallis (p<0.05) and Pearson's correlation tests. Conclusions Only in the 2nd measurement, the OCRS thickness observed was similar to the value indicated by the manufacturers; the Accufilm II and the BK28 strips showed the better marks; and no correlation was found between the thickness and the marking area.